Implementing Right to Information - Dokeniya, Anupama (World Bank, Washington, DC, 2018)
Over the last two decades, several developing countries have adopted right to information (RTI) laws, bringing the number of countries with such laws to more than 90. But empirical evidence on how effectively RTIs have worked, whether they have been effectively enforced, and if they have had any impact on improving accountability, is limited. This note examines how RTI laws have worked in different country contexts, drawing from an analysis of their implementation in eight countries spanning different regions, income levels, political forms, and administrative traditions. The experiences of these countries show that implementation has faced challenges across countries, but has been especially difficult in countries where the broader governance environment is weaker on dimensions such as the rule of law, government effectiveness, voice and accountability, civil liberties, and political rights. During the implementation phase, with the erosion of the initial political momentum behind the law, the incentives for officials to comply with the new legislation also tended to erode, resulting in efforts to undermine the law. The evidence suggests that as countries with challenging governance environments and capacity limitations adopt RTI laws, they will need to both devise implementation solutions that can adapt to these limitations and undertake complementary initiatives to strengthen their broader governance environment.